2017
DOI: 10.1016/j.apmr.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensor-Based Biofeedback Training for Balance and Gait in Parkinson Disease: A Pilot Randomized Controlled Trial

Abstract: Gamepad-based training was feasible and superior to physiotherapy without feedback in improving BBS performance and retaining it for 1 month. After training, 10MWT data were comparable between groups. Further development of the system is warranted to allow the autonomous use of Gamepad outside clinical settings, to enhance gait improvements, and to increase transfer of training effects to real-life contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
185
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(195 citation statements)
references
References 37 publications
0
185
1
1
Order By: Relevance
“…One high‐quality study evaluated virtual reality combined with treadmill training that reduced falls when compared with treadmill alone . A lower quality study using a gamepad with avatar was positive compared to physiotherapy . A lower quality study evaluating a home virtual reality device versus home conventional balance exercises was positive in both groups .…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…One high‐quality study evaluated virtual reality combined with treadmill training that reduced falls when compared with treadmill alone . A lower quality study using a gamepad with avatar was positive compared to physiotherapy . A lower quality study evaluating a home virtual reality device versus home conventional balance exercises was positive in both groups .…”
Section: Results and Conclusionmentioning
confidence: 99%
“…78 A lower quality study using a gamepad with avatar was positive compared to physiotherapy. 79 A lower quality study evaluating a home virtual reality device versus home conventional balance exercises was positive in both groups. 80 In contrast, 2 high-quality studies were negative; 1 using an avatar versus conventional balance training for balance 81 and 1 evaluating robotic gait training versus balance training.…”
Section: New Conclusion For Adjunct Therapies For Specific or Generamentioning
confidence: 99%
“…The scores obtained on the PEDro scale are shown in Table 2. Nine RCTs had high methodological quality with scores on the scale equal to or greater than 6: Picelli et al [11], Nimwegen et al [28], Volpe et al [29], Volpe et al [30], Monticone et al [31], Hashimoto et al [32], Rios Romenets et al [33], Volpe et al [34], and Carpinella et al [35]. Shujaat et al [36] and Ricciardi et al [10] scored 5, obtaining the lowest score.…”
Section: Assessment Of the Methodological Quality Of The Rcts Includementioning
confidence: 99%
“…Other long-term training studies using closed-loop visual and auditory cueing evaluated the effects of closed-loop cueing on a variety of gait parameters: gait speed [67,68,70,86,92,93], cadence [70,86], stride length [67,68,70,86], fall incidences [94], and other gait and dynamic balance measures [74,84,95] at follow-up and post-training. Only two of the long-term training studies used a wearable sensor-based, closed-loop system [86,95]. Some closed-loop training studies used augmented reality devices and game-based motion therapy for combinational cueing [72,75,77,84,96,97].…”
Section: Benefits Of Closed-loop Cueing On Gait In Pdmentioning
confidence: 99%
“…The regular practice of being upright during the training and any sustained benefits may reduce the issue of stoopness experienced by people with PD. To date, only a few closed-loop studies [70,74,86,94,95] included a randomized control trial (RCT) research design to confirm that the gait and posture improvements observed are mainly due to the presentation of cues.…”
Section: Benefits Of Closed-loop Cueing On Gait In Pdmentioning
confidence: 99%